Government’s responsibility towards investor’s loss in toll development on PPP agreements due to delay in land acquisitions - Dena Zahra Aulia; An-An Chandrawulan; Purnama Trisnamansyah (University of Merdeka Malang, 2021)
Until now, the slow process of land acquisition in toll road infrastructure development projects is still one of the obstacles to the completion of a infrastructure development project. The delay in the land acquisition process is detrimental to parties involved in PPP, especially investors. This study uses a normative juridical approach with analytical descriptive research specifications. Data collection techniques are carried out by means of literature study to obtain secondary data and interviews to obtain primary data, then the data obtained is analyzed using qualitative juridical methods, namely by taking inventory, systematically arranging, connecting with each other related to the problems studied with the enactment of the provisions of the regulations. one does not conflict with other regulations. The result of this research is a form of responsibility from the Government due to delays in land acquisition, namely compensation in the form of extension of the concession period on a toll road project with a PPP scheme, and consideration of additional initial tariffs on toll roads based on inflation, capital, construction time and increase. the concession period and also the imposition of fines in a business contract, and the last resort for resolving disputes over the PPP agreement through non-litigation or arbitration institutions based on Presidential Regulation Number 38 of 2015.How to cite item: Aulia, D. Z., Chandrawulan, AA., Trisnamansyah P. (2021). Government’s responsibility towards investor’s loss in toll development on PPP agreements due to delay in landa cquisitions. Jurnal Cakrawala Hukum, 12(1), 21-31.doi:10.26905/idjch.v12i1. 4337.